2018
DOI: 10.7554/elife.38539
|View full text |Cite
|
Sign up to set email alerts
|

INAVA-ARNO complexes bridge mucosal barrier function with inflammatory signaling

Abstract: Homeostasis at mucosal surfaces requires cross-talk between the environment and barrier epithelial cells. Disruption of barrier function typifies mucosal disease. Here we elucidate a bifunctional role in coordinating this cross-talk for the inflammatory bowel disease risk-gene INAVA. Both activities require INAVA’s DUF3338 domain (renamed CUPID). CUPID stably binds the cytohesin ARF-GEF ARNO to effect lateral membrane F-actin assembly underlying cell-cell junctions and barrier function. Unexpectedly, when boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 41 publications
2
29
0
1
Order By: Relevance
“…Indeed, recent additional studies have shown that expression of C1orf106/INAVA modulates ARNO (GTP-Arf6 GEF) regulation of MDP-induced NOD2 activation. 51 The cellular mechanisms and structural basis by which MDP directly binds NOD2 and GTP-Arf6 is unknown and ongoing in our laboratory, which should provide important insights into innate immune activation and intestinal barrier homeostasis. As bacterial pathogens such as Salmonella enterica serovar Typhimurium 47 and enterohaemorrhagic Escherichia coli 48 inject proteins into host cells that modulate or directly bind Arf GTPases, these bacterial virulence factors may also suppress innate immune detection by interfering with MDP binding to NOD2 and GTP-Arf6, which should also be an interesting area of future investigation in pathogen immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent additional studies have shown that expression of C1orf106/INAVA modulates ARNO (GTP-Arf6 GEF) regulation of MDP-induced NOD2 activation. 51 The cellular mechanisms and structural basis by which MDP directly binds NOD2 and GTP-Arf6 is unknown and ongoing in our laboratory, which should provide important insights into innate immune activation and intestinal barrier homeostasis. As bacterial pathogens such as Salmonella enterica serovar Typhimurium 47 and enterohaemorrhagic Escherichia coli 48 inject proteins into host cells that modulate or directly bind Arf GTPases, these bacterial virulence factors may also suppress innate immune detection by interfering with MDP binding to NOD2 and GTP-Arf6, which should also be an interesting area of future investigation in pathogen immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hearing-related genes, our genome-wide screen also revealed bat-specific selection on several immunity-related genes: the B-cell-specific chemokine CXCL13 45 , the asthma-associated NPSR1 46 and INAVA, a gene that is involved in intestinal barrier integrity and enhancing NF-κB signalling in macrophages 47 . Changes in these genes may have contributed to the unique tolerance of pathogens among bats 3 .…”
Section: Screens For Gene Selection Losses and Gainsmentioning
confidence: 93%
“…INAVA encodes an immunity-related protein with a dual role in innate immunity. In intestinal epithelial cells, this gene is required for intestinal barrier integrity and the repair of epithelial junctions after injury 65,66 . Consistent with these functions, mutations in human INAVA are associated with inflammatory bowel disease 67 , a disorder characterized by chronic inflammation of the gastrointestinal tract and an increased susceptibility to microbial pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these functions, mutations in human INAVA are associated with inflammatory bowel disease 67 , a disorder characterized by chronic inflammation of the gastrointestinal tract and an increased susceptibility to microbial pathogens. In macrophages, INAVA amplifies an IL-1β-induced pro-inflammatory response by enhancing NF-kB signalling 66 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation